Productivity improvement for furniture industry by using witness simulation software - Tee, Chun Teck (2010)
A furniture industry typically involves a number of stages, including receiving raw materials, cutting, sanding, laminating, shaping, drilling, brushing, assembly, and finishing. The longer of process cycle time, the frequent of machine downtime, and the poor layout of the factory have added to the complexity and challenges of furniture industry. With respect to the project title, Productivity Improvement for Furniture Industry by using WITNESS Simulation Software, Lein Hua Furniture Industry Sdn. Bhd. (LHF) has been selected to be improved. The objective for LHF has always been to achieve better productivity, reduce the processing time, minimize the machine downtime, and meet regulatory requirements. This study focuses on applying simulation method to improve the operations in the LHF industry. Therefore, the project objectives can be briefly explained as to design and improve the floor layout of LHF, analyze the designed layout and select the best solution. The project is started by evaluating and identifying the problems existed in the industry, continued by data collection for the data analysis and proceeds to applying simulation modelling step. Meantime, there are three alternatives for improving productivity are suggested and the best of it to be chosen. By running an experiment on the suggested alternatives to improve the output of chairs, these alternatives are modeled in the WITNESS Simulation software and run for the experimental time of 8 hours. These results are analyzed by Kruskal-Wallis and one way ANOVA test for the best solution selection. The experimented results are then being compared with the Cost-Effectiveness Analysis to determine the most efficient layout that are able to produce high output of chairs with lowest cost. From the findings, the most productivity improvement method is the Alternative 3, which is additional of a Laminating machine and reduction of a Brushing machine, as well as combination of Sanding II and Sanding III process after Drilling process. This approach increases the daily output of chairs from 44 to 46 units and the cost of chair per unit from RM45.53 reduced to RM43.63. Therefore, the objectives of this project have been achieved and the selected alternative will be proposed to the LHF for implementation.